A Novel Frame-Shift Mutation in SCNN1B Identified in a Chinese Family Characterized by Early-Onset Hypertension - Lu, Yi-Ting; Liu, Xin-Chang; Zhou, Ze-Ming; Zhang, Di; Sun, Lin; Zhang, Ying; Fan, Peng; Zhang, Lin; Liu, Ya-Xin; Luo, Fang; Zhou, Xian-Liang (Frontiers in Cardiovascular Medicine, 2022)
Background Liddle syndrome is a form of monogenic hypertension caused by mutations in the three homologous subunits of the epithelial sodium channels (ENaCs), α, β, and γ. It is characterized by early-onset refractory hypertension, hypokalemia, low renin activity, and hypoaldosteronism. In this study, we report a novel frame-shift mutation in SCNN1B responsible for Liddle syndrome in a Chinese family. Methods DNA samples were collected from all participants. Whole-exome sequencing was performed in the proband to detect possible causative variants. Sanger sequencing was then conducted in the other family members to verify the candidate variant, and in 100 patients with hypertension and 100 normotensive controls to exclude population genetic polymorphism. Results We identified a novel frame-shift mutation (c.1691_1693delinsG) in SCNN1B that was responsible for Liddle syndrome in this family. This mutation leads to the substitution of Arg in place of Gln at codon site 564 and generates a new stop codon at 592, influencing the crucial PY motif and resulting in reduced inactivation of the ENaCs. Aside from the proband, eight family members carried the mutation. Intra-familial phenotypic heterogeneity was observed in the blood pressure and serum potassium levels. Amiloride therapy combined with a low sodium diet is effective to alleviate the symptoms of patients with Liddle syndrome. Conclusion c.1691_1693delinsG, a novel frame-shift mutation in the β subunit of ENaC, was identified in a Chinese family with Liddle syndrome by whole-exome sequencing. Phenotypic heterogeneity can make diagnosis of Liddle syndrome difficult on the basis of clinical or biochemical characteristics alone. Genetic analysis is a useful tool allowing timely and accurate diagnosis of Liddle syndrome and playing a guiding role in precise treatment of the disease.